The effect of public work programme in Hungary on private sector wages - Lajos Tamás Szabó (Magyar Nemzeti Bank, 2020)
The public work (PW) programmes have been the major active labour market policy tools since 2011 in Hungary. Majority of the public workers were inactive before the programme. Due to this the labour supply considerably increased in those district, which got significantly more subsidy from the central government for PW programmes. Large portion of the public work funds was distributed to those districts, which were below the country average development level. As the programme budget was not evenly distributed among districts, I can use this as variation to identify the indirect effect of the programme on the private sector. I estimate the effect of public work programmes on the private sector wage using regression discontinuity design. According to my estimations the private sector wage level is lower on average by 9% between 2013-2017 among the low-skilled workers in those districts where the number of public workers is higher. In the mean time in these district the private sector employment dynamics is 4% higher. This gives a (-0.43) elasticity of labour demand, which is in-line with the previous estimates for Hungary.
Keywords: J21; J31; J38; 330; local labour markets; labour supply; wage differentials